2016
DOI: 10.1016/j.watres.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A metabolism perspective on alternative urban water servicing options using water mass balance

Abstract: Please cite this article as: Farooqui, T.A., Renouf, M.A., Kenway, S.J., A metabolism perspective on alternative urban water servicing options using water mass balance, Water Research (2016Research ( ), doi: 10.1016Research ( /j.watres.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The theory and concept of urban water metabolism includes a wide range of performance implications, changing from resource efficiency and hydrological performance of different water servicing options in Australia (Farooqui et al 2016), to ecological relationships among different UWS sectors and their wastewater discharges in China (Zheng et al 2019). The integration of urban metabolism and the nexus approaches for performance assessment in real-world systems has not been employed substantially.…”
Section: Introductionmentioning
confidence: 99%
“…The theory and concept of urban water metabolism includes a wide range of performance implications, changing from resource efficiency and hydrological performance of different water servicing options in Australia (Farooqui et al 2016), to ecological relationships among different UWS sectors and their wastewater discharges in China (Zheng et al 2019). The integration of urban metabolism and the nexus approaches for performance assessment in real-world systems has not been employed substantially.…”
Section: Introductionmentioning
confidence: 99%
“…; Farooqui et al. ). Moreover, the latest UWMF still does not include components such as system loss, which is a significant flow component of a UWMF (30% to 50%) in developing countries and also in some other parts of the world (CSE ; Kingdom et al.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The framework included alternative sources of water such as rainwater, surface runoff, wastewater, decentralized water supply, evapotranspiration, and groundwater infiltration. Recently, this framework was further refined by Farooqui and colleagues () by incorporating other flows such as decentralized recycled water within and outside an urban system. But Renouf and colleagues () reported that the framework has further scope to develop by incorporating water use for ecosystem services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While the visions are articulated in different ways (Table A1), some consistencies are evident in the key objectives, including access to water and sanitation, supply security, environmental protection, the functionality of urban water, risk management of extreme conditions (resilience to droughts and floods) and institutional aspects (Table 1). They focus on the management of direct water (real flows of water from surrounding regions) and not on indirect water (that embodied in the goods and services produced using water from elsewhere) (Renouf and Kenway 2016).When existing performance indicators are compared to the objectives derived from the vision statements (Table 1) we find a misalignment.…”
Section: Introductionmentioning
confidence: 96%